THE ROLE OF ACTRESS AND MORALS TEACHERS IN DEVELOPING THE MORALS OF STUDENTS AT AISYIYAH BUSTANUL ATHFAL 91 KINDERGARTEN, RAWALUMBU DISTRICT, BEKASI CITY - Rosminah; M Nasor; Mujiatun (UNISAN JURNAL, 2025)
This study aims to describe the role of Islamic Religious Education (PAI) teachers in fostering students’ morals at Muzammil Al-Aziziyah Private Junior High School. Students’ morals are one of the important indicators in the success of education, especially at the junior high school level, where students are in a transitional period of moral and character development. PAI teachers have the responsibility not only in delivering religious material, but also in guiding, instilling, and internalizing the values ​​of akhlakul karimah in students. This study uses a descriptive qualitative method with data collection techniques through observation, interviews, and documentation. The results of the study indicate that the role of PAI teachers in fostering students’ morals is carried out through several strategies, including being a role model in daily behavior, providing learning that is integrated with religious practices, and conducting coaching and habituation of religious activities such as congregational prayer, reading the Qur’an, and reciting the Koran. In addition, teachers are also active in providing advice, motivation, and constructive reprimands to students who experience behavioral deviations. The obstacles faced include lack of parental support, negative social environment influences, and limited time in moral development at school. Nevertheless, the role of Islamic Religious Education teachers consistently provides positive contributions in shaping the morals of students at Muzammil Al-Aziziyah Private Middle School.